Transcriptomic Analysis of the Effects of Chemokine Receptor CXCR3 Deficiency on Immune Responses in the Mouse Brain during Toxoplasma gondii Infection - Kousuke Umeda (MDPI AG, 2021)
The obligate intracellular parasite Toxoplasma gondii infects warm-blooded animals, including humans. We previously revealed through a whole-brain transcriptome analysis that infection with T. gondii in mice causes immune response-associated genes to be upregulated, for instance, chemokines and chemokine receptors such as CXC chemokine receptor 3 (CXCR3) and its ligand CXC chemokine ligand 10 (CXCL10). Here, we describe the effect of CXCR3 on responses against T. gondii infection in the mouse brain. In vivo assays using CXCR3-deficient mice showed that the absence of CXCR3 delayed the normal recovery of body weight and increased the brain parasite burden, suggesting that CXCR3 plays a role in the control of pathology in the brain, the site where chronic infection occurs. Therefore, to further analyze the function of CXCR3 in the brain, we profiled the gene expression patterns of primary astrocytes and microglia by RNA sequencing and subsequent analyses. CXCR3 deficiency impaired the normal upregulation of immune-related genes during T. gondii infection, in astrocytes and microglia alike. Collectively, our results suggest that the immune-related genes upregulated by CXCR3 perform a particular role in controlling pathology when the host is chronically infected with T. gondii in the brain.